Michael Weiss and Hassan Hassan, ISIS: Inside the Army of Terror - Ms. Hajira Asaf Khan (CISS Insight Journal, 2015)
ISIS: Inside the Army of Terror, gives a thorough analysis of Islamic State (IS) and its operational strategies in Iraq and Syria. Co-authored by Michael Weiss and Hassan Hassan, both experts on Middle Eastern policy, and among some of the most well-known names in policy analyses, the authors are well equipped to deal with the subject. One of the authors of the book, Hassan Hassan, is from Syria, a country affected by the brutal regime of IS. Spread out over fourteen chapters, the book pans out from the very beginning of the story of what we now know as “The Islamic State”. The first two chapters deal with bringing out a character sketch of Abu-Musab al-Zarqawi the “Founding Father” of IS. Zarqawi’s personal and political history is discussed, setting the tone for the book and also of the nature of the “terrorist organization” that he subsequently fathered. The second chapter moves on to unravelling his ideological differences with Osama bin Laden. Zarqawi considered Bin Laden’s brand of jihadism as weak and flawed. Later on, this difference was seen more clearly as the conduct of Al-Qaeda—which served as the initial recruiting and training ground for modern-day ISIS fighters before its leadership parted ways with Al-Qaeda and morphed into a strikingly different and more brutal organization in comparison, with AlQaeda, in Syria ans Iraq. This can, in the opinion of the writers, be attributed to the difference of opinion that Zarqawi had with his contemporaries on policy issues with other Jihadists around the world.